Editorial [ Purine Binding Proteins as Anti-Cancer Targets Guest Editor: Dr. Zhenhai Gao ] - Gao, Zhenhai (Current Topics in Medicinal Chemistry, 2006)
The explosion of genomic information has led to the identification of a plethora of genes that are responsible for the malignant phenotypes of human cancers. Over the past two decades, the new paradigm and strategy in cancer therapy has been to develop agents that specifically target key molecules and signaling pathways involved in tumor growth and progression. The molecularly targeted therapy is widely expected to hold the potential of providing a much improved risk/benefit ratio, compared with conventional cytotoxic chemotherapy. A prominent class of such targets, perhaps one of the most abundant target sources for oncology drug discovery, is the protein kinase family. ATP binding kinases play pivotal roles in oncogenic signal transduction. Indeed, the recent approval of several kinase inhibitors including Gleevec, Iressa, Tarceva, Nexavar and Sutent has firmly established the eminent drugability of protein kinases. We know now that the human genome might encode as many as 518 protein kinases, and about 20-30% of pharmaceutical discovery programs are currently focused on various kinases. However, kinases are only part of a larger family of purine binding proteins in human genome, collectively called